Promising approaches to address the needs of poor female farmers - Quisumbing, Agnes R.; Pandolfelli, Lauren (International Food Policy Research Institute, 2008)
Gender norms are an important constraint to increasing agricultural productivity. Inequality in the distribution of resources between men and women is linked with production inefficiency, yet interventions targeting smallholder farmers often fail to redress women's lack of access to, and control of, important agricultural resources. Women are often constrained in access to and control of land, water, and other natural resources; complementary inputs, such as seeds and fertilizer; new varieties and technologies; agricultural extension; labor; credit; markets; and social capital. Oftentimes, interventions will be designed to relieve one constraint, not realizing that gender norms-or constraints in other resources-are more binding and may affect the outcome of the intervention. Without specific attention to gender issues, programs and projects are likely to reinforce inequalities between women and men and may even increase resource imbalances. While individual projects cannot hope to redress these inequalities in the short term, at a minimum, interventions should do no harm, and ideally they should catalyze a change process for ending gender discrimination and securing women's access to key resources. This brief focuses on key agricultural resources needed by poor female farmers to generate incomes and ensure their families' food security. It is organized around key resources and promising approaches to increase poor women's control of those resources. One resource that is not included in this review is human capital. It must be emphasized that investing in women's education, health, and nutrition is an integral part of enabling women to guarantee their families-and their own-well-being. These approaches were identified in the course of a review of projects and interventions in Sub-Saharan Africa and South Asia. However, while many of these interventions are innovative, most of them have not been rigorously evaluated. Where evaluations have been done, little attention has been paid to the differential impacts on men and women, or to which delivery mechanisms may be more effective in reaching different groups of women and men. Many of the approaches were also pilot projects, and without evaluations it is difficult to recommend which of them should be scaled up. Nevertheless, this brief suggests many promising strategies for channeling resources into the hands of female farmers to boost their agricultural productivity.